تداعيات الأزمة السورية على قطاع التجارة الخارجية مع تركيا (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يدرس هذا البحث تأثير الأزمة السورية على قطاع التجارة الخارجية (واردات وصادرات) مع تركيا, من خلال اجراء مقارنة لتطور الصادرات والواردات السورية التركية خلال فترة ست سنوات قبل الأزمة وست سنوات خلال الأزمة, وتطرح مشكلة البحث التساؤلات الآتية: ما هو حجم التبادلات التجارية بين سورية وتركيا قبل الأزمة؟, وما التغيرات الحاصلة على التبادلات التجارية خلال الأزمة السورية؟. وقد تركزت أهداف البحث على إظهار الأثر الحقيقي للأزمة السورية على العلاقات الاقتصادية السورية التركية من جانب الميزان التجاري (واردات وصادرات). و قد خلص الباحث إلى عدة نتائج وتوصيات منها: انخفاض حجم التبادلات التجارية بين سورية وتركيا بشكلٍ كبيرٍ بسبب الموقف العدائي والسلبي للدولة التركية تجاه الشعب السوري والحكومة السورية وبسبب قطع العلاقات السياسية والدبلوماسية واغلاق الحدود بين البلدين, ومهما تطورت العلاقات الاقتصادية بين البلدين تبقى محكومة من قبل القرار السياسي والعلاقات السياسية بين البلدين, وقد اتجهت سورية لتعويض الانخفاض في الميزان التجاري مع تركيا إلى دول أخرى كالعراق والصين وايران وروسيا, وقد تضرر الاقتصاد السوري وأيضاً الاقتصاد التركي بسبب انخفاض التبادلات التجارية بين البلدين. This research studies the impact of the Syrian crisis on the foreign trade sector (imports and exports) with turkey through a comparison of the development of Syrian Turkish exports and imports during the period of six years before the crisis and six years during the crisis. The problem of this research leads us to ask the following questions: what is the volume of trade exchanges between Syria and turkey before the crisis? What is the changes are taking place during the Syrian crisis? The objectives of the research were focused on showing the real impact of the Syrian crisis on the Syrian-Turkish economic relation on the balance of trade, The researcher reached several results and recommendations  including: - the volume of commercial exchanges between Syria and turkey has been greatly reduced due to the hostile and negative attitude of the Turkish state toward the Syrian people and the Syrian government and the severing of political and diplomatic relations and the closure of the border between the two countries. No matter how economic relations developed between procreation governed by the political decision and political relations between the countries . Syria has tended to compensate for the decline in the trade balance with turkey to other countries such as Iraq, china, Iran, and Russia, the Syrian economy and the Turkish economy have been affected by the decrease in trade exchanges between the two countries.